2011
DOI: 10.1016/j.ygyno.2011.02.032
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for HPV infection among American Indian and white women in the Northern Plains

Abstract: Objective American Indian (AI) women living in the Northern Plains have high incidence and mortality rates for cervical cancer. We assessed risk factors for human papillomavirus (HPV) infection among AI and White women. Methods We tested cervical samples for HPV infection obtained from women ages 18-65 years attending 2 rural AI reservation clinics in South Dakota (n = 235) and an urban clinic serving predominantly White women (n = 246). Patients self-reported information on HPV risk factors. We used percent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
3

Year Published

2013
2013
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 13 publications
0
26
0
3
Order By: Relevance
“…Other than age, no other risk factors evaluated were significantly associated with hrHPV infection. To our knowledge, only one other study has evaluated risk factors for prevalent HPV infection in American Indian women [15]. In that study, which assessed women in the Northern Plains, age and current smoking were the only risk factors independently associated with HPV infection, with age inversely associated and smoking positively associated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other than age, no other risk factors evaluated were significantly associated with hrHPV infection. To our knowledge, only one other study has evaluated risk factors for prevalent HPV infection in American Indian women [15]. In that study, which assessed women in the Northern Plains, age and current smoking were the only risk factors independently associated with HPV infection, with age inversely associated and smoking positively associated.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies suggest that the epidemiology of HPV infection may differ between American Indian and non-Hispanic White women [15, 16, 17], but data on American Indian populations are scarce, and no study to date has focused specifically on Hopi women. Defining the epidemiology of hrHPV in a range of American Indian populations is essential for evaluating whether disparities in cervical cancer incidence result from differences in the prevalence of hrHPV infections.…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological studies have consistently reported that the risk of genital HPV infection seems to increase with number of recent/lifetime sexual partners and age at sexual debut (Ho et al, 1998;Richardson et al, 2000;Moscicki et al, 2001;Winer et al, 2003;Bell et al, 2011;Bahmanyar et al, 2012). Increased metaplastic activity in the cervix during adolescence and its decline after menopause implica earlier age at sexual debut as a risk factor for HPV infection.…”
Section: Epidemiology Of Human Papillomavirus Infectionsmentioning
confidence: 99%
“…Em outros estudos, a maior parte realizados com indígenas e aborí-gines de outros países, foram encontradas taxas que variaram de 19,3% a 37,5% 16,17,18,28,29 . A vulnerabilidade das mulheres Panará está relacionada ao início da atividade sexual, por volta dos 12 anos de idade, de frequentemente possuírem mais de um parceiro e terem taxa de fecundidade total de 7,3 filhos por mulher 30 .…”
Section: Discussionunclassified